Integrating qualitative interviews in drug development and the use of qualitative evidence in product labelling and health technology assessments: a review - Michel, Anne-Sophie; Kamudoni, Paul; Marrel, Alexia; Adiutori, Rocco; Desvignes-Gleizes, Céline; Lanar, Sally; Schache, Peter; Spies, Erica; Park, Josephine (Frontiers in Medicine, 2023)
Objective Including qualitative research in clinical trial design is an innovative approach to understanding patients’ perspective and incorporate the patient’s voice in all stages of drug development and evaluation. This review aims to explore current practices, lessons learned from the literature, as well as how qualitative interviews are considered by health authorities for marketing authorization and reimbursement. Methods A targeted literature review of Medline and Embase databases was conducted in February 2022 to identify publications on qualitative methods embedded in clinical trial of pharmaceutical products. An additional search of guidelines and labeling claims of approved products regarding qualitative research was performed in various sources of grey literature. Results From the 24 publications and nine documents reviewed, we identified the research questions addressed with qualitative methods during clinical trials (e.g., change in quality of life, symptoms assessment, treatment benefit), preferred data collection methods (e.g., interviews), and data collection points (e.g., baseline and exit interviews). Moreover, the data from labels and HTAs demonstrate that qualitative data can play an important role in approval processes. Conclusion The use of in-trial interviews is still emerging and is not yet common practice. Although the industry, scientific community, regulatory agencies and HTAs are showing an increasing interest in the use of evidence generated via in-trial interviews, guidance from regulators and HTAs would be helpful. Developing new methods and technologies to address the common challenges for such interviews is key to progress.